2019
DOI: 10.1016/j.nbd.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation impairs cognitive flexibility and alters transcription in frontal cortex

Abstract: Background: Epidemiological studies suggest that the risk of neurodevelopmental disorders such as autism spectrum disorder (ASD) and schizophrenia is increased by prenatal exposure to viral or bacterial infection during pregnancy. It is still unclear how activation of the maternal immune response interacts with underlying genetic factors to influence observed ASD phenotypes. Methods: The current study investigated how maternal immune activation (MIA) in mice impacts gene expression in the frontal cortex in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 75 publications
3
27
0
Order By: Relevance
“…RNA analysis of fetal brains in the period following the MIA led to several compelling insights and revealed extensive dysregulation in gene sets related to brain and neuronal development. To our knowledge, this is the first time that RNA-seq has been performed during this time period of mouse development following MIA, as most gene expression studies have considered only the adult offspring of MIA 66 68 . Since fetal brain tissue at this stage is scant, our results provide information at the level of gene enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…RNA analysis of fetal brains in the period following the MIA led to several compelling insights and revealed extensive dysregulation in gene sets related to brain and neuronal development. To our knowledge, this is the first time that RNA-seq has been performed during this time period of mouse development following MIA, as most gene expression studies have considered only the adult offspring of MIA 66 68 . Since fetal brain tissue at this stage is scant, our results provide information at the level of gene enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in rodents, externally triggering a maternal immune response during pregnancy induces behavioural alterations in adult offspring. These include reduced cognitive flexibility and decreased social exploration, traits of an ASD-like phenotype (7072). In humans, increased odds of neonatal infections were reported for children with ASD (73).…”
Section: Discussionmentioning
confidence: 99%
“…Malkova et al found that poly(I:C) injection during pregnancy resulted in offspring exhibiting the core symptoms of ASD: decreases in sociability and communication and increases in repetitive/stereotypic behaviours [21]. These findings were reproduced by subsequent studies and extended to include other ASD-related symptoms, establishing construct and face validity [10,11,22]. The range of animal models of MIA continues to expand, with more recent models using exposures to Staphylococcal enterotoxin [23], toll-like receptor 7 agonists [24], and allergens [25].…”
Section: Animal Models Of Maternal Immune Activation (Mia)mentioning
confidence: 95%
“…Meta-analyses and epidemiological studies have reported an association between maternal infection and incidence of ASD in the offspring [ 6 , 7 , 8 ], and certain in utero inflammatory markers have been associated with ASD [ 6 ]. Animal studies of maternal immune activation (MIA) have characterised a prominent pro-inflammatory phenotype with is associated with impairments in communication and stereotypic behaviours [ 9 , 10 , 11 , 12 , 13 ]. Furthermore, transcriptomic and cytokine profiling studies in individuals with ASD have also revealed a state of immune dysregulation and elevated pro-inflammatory cytokines [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%